ANALISIS RETURN ON INVESTMENT (ROI), EARNING PER SHARE (EPS) DAN DEVIDEND PER SHARE (DPS) PADA PERUSAHAAN SUB SEKTOR KOSMETIK YANG GO PUBLIC DI BURSA EFEK INDONESIA - Pemy Christiaan (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2020)
This study aims to determine the Return On Investment (ROI), Earning Per Share (EPS), and Dividend Per Share (DPS) in Cosmetics Sub Sector Companies that Go Public on the Indonesia Stock Exchange 2016-2019 Period. The research method used in this research is a quantitative method which is carried out in descriptive form. Data analysis uses the ratio of Return On Investment (ROI), Earning Per Share (EPS), and Dividend Per Share (DPS). The results showed that the analysis of the overall return on investment (ROI) ratio did not meet the standard ROI ratio of 30%. For the analysis of the Earning Per Share (EPS) ratio of all sub-sector companies, it has met the EPS standard, which is 20%, while the results of the analysis of the average value of the dividend per share (DPS) ratio are in the very efficient category even though there are 3 companies that do not distribute dividends.